PENGARUH ARUS KAS TERHADAP LIKUIDITAS PADA KPRI SINAR MURNI KABUPATEN BREBES - Ulul Absor (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2017)
Abstract This study entitled the Effect of Cash Flow on Liquidity at KPRI Sinar Murni Brebes Regency. The formulation of the problem in this study is how cash flows at KPRI Sinar Murni Brebes Regency, how the level of liquidity at KPRI Sinar Murni Brebes Regency and how the effect of cash flow on liquidity on KPRI Sinar Murni Brebes Regency. The form of research used in this study is quantitative descriptive research. Descriptive research tries to explain how the development of cash flow and liquidity at KPRI Sinar Murni Brebes Regency. Quantitative research in this study calculates and analyzes with simple linear regression analysis to determine the effect of cash flow independent variables on liquidity dependent variables during the 2011 to 2016 research period, with the following results: 1. Cash Flow Analysis Operating cash flow fluctuated, in 2011 the negative cash flow balance was Rp. 412,787,887.08 so also for 2016 the negative cash flow balance of Rp. Rp. 124,992,768.70 while for 2011,2012 cash flow balances rose later in 2014 and 2015 the cash flow balance decreased. 2. Liquidity Analysis The liquidity ratio based on the fast ratio (acid test ratio) has an average of 437.48% according to the Decree of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 129 of 2012 concerning Guidelines for Classification of Liquidity Cooperatives 437.48% including unfavorable criteria because it is bigger of 275% while the standard liquidity ratio is theoretically 200% or 2: 1. 3. Hypothesis Testing. Based on the results of the t-test the probability number of cash flow variables is 0.035 smaller than the significance probability number 0.05, so Ho is rejected and Ha is accepted. Likewise, the value of t arithmetic is 3.123 greater than t table 2.571 or (3.123> 2.571) so that the hypothesis that cash flow influences liquidity at KPRI Sinar Murni Regency of Brebes is acceptable.